A review of the reproductive toxicity of environmental contaminants in Caenorhabditis elegans - Yunjiang Yu; Haibo Chen; Xin Hua; Chen Wang; Chenyin Dong; Dongli Xie; Shihui Tan; Mingdeng Xiang; Hui Li (Elsevier, 2022)
The release of several environmental pollutants poses a potential threat to the several ecosystems and humans. Reproductive toxicity represents one of the most significant toxic effects of environmental contaminants. It is necessary to assess reproductive toxicity and the mechanisms underlying environmental toxicity in organisms. Because of its unique features in toxicology research, Caenorhabditis elegans is an important animal model used for the toxicity assessment of environmental contaminants. In this review, we introduce the reproductive toxicity and mechanisms underlying the actions of environmental contaminants, including heavy metals, organic pollutants, particulate matter, microplastics, nanomaterials, and irradiation. Moreover, we have put forth some perspectives about toxicity assessments, transgenerational toxicity, and toxicological mechanisms of environmental contaminants in the future.